THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND ELECTRONIC WORD OF MOUTH ON EMINA PRODUCT PURCHASE DECISIONS (Case Study on UNPAB Management Study Program Students Class of 2020) - Nita Salsabila; Annisa Sanny (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to test and find out more clearly "The Effect of Product Quality, Price, and Electronic Word of Mouth on Purchasing Decisions for Emina products (Case Study on UNPAB Management Students class of 2020)". This study uses a quantitative method involving 78 respondents. data collection was carried out using the distribution of questionnaires via google form. The data obtained was analyzed with a statistical formula, namely by using multiple linear regression analysis which was processed using the SPSS version 20 program. The results of quantitative research indicate that Product Quality, Price, and Electronic Word of Mouth partially have a positive and significant effect on Emina Product Purchasing Decisions. and Product Quality, Price, Electronic Word of Mouth simultaneously have a positive and significant effect on Emina Product Purchasing Decisions.